Subsidiary Initiative Taking in Multinational Corporations: The Relationship between Power and Issue Selling. Issue 9 (September 2016) - Dörrenbächer, Christoph; Gammelgaard, Jens
This paper investigates the political maneuvering that accompanies subsidiary initiative taking in multinational corporations. On the basis of an explorative empirical investigation of subsidiary initiative taking in the French subsidiaries of six German MNCs, the paper explores the activities that subsidiaries undertake to sell their initiatives, and the relationships among issue selling, subsidiary power and headquarters' hierarchical power. The findings suggest that the use of issue-selling tactics is common when subsidiaries engage in initiative taking. In addition, the paper demonstrates that a low degree of issue selling is needed to obtain approval of an initiative in less asymmetrical headquarters–subsidiary power relationships (i.e. relationships in which subsidiaries are relatively powerful). In cases where power relationships are highly asymmetrical, issue selling is a necessity, but it is hardly a sufficient condition for obtaining headquarters' approval. This renders issue selling to a second-rank power in subsidiary initiative taking, as it only works in conjunction with subsidiary power.